Impact of Plantago ovata Forsk leaf extract on morpho-physio-biochemical attributes, ions uptake and drought resistance of wheat (Triticum aestivum L.) seedlings - Alharbi, Khadiga; Alhaithloul, Haifa Abdulaziz Sakit; Alayafi, Aisha A. M.; Al-Taisan, Wafa’a A.; Alghanem, Suliman Mohammed; Al-Mushhin, Amina A. M.; Soliman, Mona H.; Alsubeie, Moodi Saham; Vodnar, Dan C.; Marc, Romina Alina (Frontiers in Plant Science, 2022)
The use of Plantago ovata Forsk leaf is a novel approach to combat with drought stress and can be a beneficial method to tolerate against drought stress in cereal crops. In this study, the influence of various P. ovata extract i.e., [water spray (WS), 0 (no P. ovata), 10, 20, 30 and 40%] on the seed germination, growth-related attributes, photosynthetic efficiency, stomatal properties, mineral status of the plants, oxidative machinery and response of enzymatic compounds were investigated under the drought stressed environment and normal water spay in wheat (Triticum aestivum L.) seedlings. Our findings depicted that the water deficit condition declined the crop growth, photosynthetic efficiency, stomatal properties, and nutritional status of the plant. However, Drought stressed condition enhanced the indicators of oxidative stress, enzymatic antioxidants and non-enzymatic antioxidants in T. aestivum seedlings. Our findings also advocated that the effect of P. ovata extract significantly enhanced seed germination, growth-related attributes, photosynthetic efficiency, stomatal properties, mineral status of the plants and antioxidant machinery by decreasing the oxidative stress in the drought stressed T. aestivum seedlings. Hence, the use of P. ovata extract are useful and can be applied to give fortify with nutrients to overcome abiotic stress in water deficit environment.